"We aren't your reincarnation!" workplace motivation across X, Y and Z generations. Issue 1 (17th June 2020) - Mahmoud, Ali B.; Fuxman, Leonora; Mohr, Iris; Reisel, William D.; Grigoriou, Nicholas
Abstract : Purpose: The primary purpose of this research is to examine generational differences in valuing the sources of employees' overall motivation in the workplace across Generation X, Generation Y and Generation Z with a view of assisting managers in making employment decisions and maintaining multigenerational staff. Design/methodology/approach: The respondents in the study live and work in Canada and provided answers to self-administered online surveys between the fourth quarter of 2017 and the end of January 2020. To assess subjects' work motivation, the study employed Gagné et al. 's (2014) multidimensional work motivation scale (MWMS) alongside a three-item measure of employees' overall motivation (designed for this study). The authors assessed measures of validity and reliability and tested the hypothesis about generational differences in work motivation using structural equation modelling (SEM). Findings: The six motivators regress differently to employees' overall motivation. Generation Z is more sensitive to amotivation than Generation X and Generation Y. Extrinsic regulation-material is a valid source of overall work motivation for Generation Z only. Only Generation X values extrinsic regulation-social as a source of employees' overall motivation. So is introjected regulation by Generation Y. Unlike Generation Z, both Generation X and Generation Y employees value identified regulation as a source of overall work motivation. Finally, intrinsic motivation contributes more to Generation Z employees' overall work motivation than it does for Generation X and Generation Y. Research limitations/implications: Further work needs to be done to establish whether variations in valuing the sources of motivation may also be spawned by age or status of the respective groups. Future investigations can expand the authors' focal theme to include additional organisational outcomes, alternative geographical settings and/or include country's economic development as an additional variable. Moreover, further research can address the implications of national culture on shaping generational differences in employee's motivation as well as aiding companies to redesign work tasks considering today's uncertainty as well as increasingly competitive, global environment (e.g. the rise of artificial intelligence). Practical implications: It is vital to offer motivators that are valued by each of the three generations, i.e. X, Y and Z, before being able to attract the best candidates of each generation. Organisations should not only create an inclusive and understanding multigenerational working environment but also be able to communicate strong branding via new communication channels successfully (e.g. social media networks), which Generation Yers and Generation Zers utilise better than any other generation in employment. Finally, the authors suggest that service organisations with diverse generational composition should adopt new measures of workplace agility to survive interminable disruptions (e.g. the coronavirus disease 2019 [COVID-19] pandemic). Originality/value: This is the first study of its kind to examine generational differences between Generation X, Generation Y and Generation Z in valuing workplace motivation from a western cultural perspective.